Cell-specific functions of androgen receptor in skeletal muscles - Hiroshi Sakai; Yuuki Imai (Endocrine Journal)
Androgens play a vital role not only in promoting the development of male sexual characteristics but also in exerting diverse physiological effects, including the regulation of skeletal muscle growth and function. Given that the effects of androgens are mediated through androgen receptor (AR) binding, an understanding of AR functionality is crucial for comprehending the mechanisms of androgen action on skeletal muscles. Drawing from insights gained using conditional knockout mouse models facilitated by Cre/loxP technology, we review the cell-specific functions of AR in skeletal muscles. We focus on three specific cell populations expressing AR within skeletal muscles: skeletal muscle cells, responsible for muscle contraction; satellite cells, which are essential stem cells contributing to the growth and regeneration of skeletal muscles; and mesenchymal progenitors, situated in interstitial areas and playing a crucial role in muscle homeostasis. Furthermore, the indirect effects of androgens on skeletal muscle through extra-muscle tissue are essential, especially for the regulation of skeletal muscle mass. The regulation of genes by AR varies across different cell types and contexts, including homeostasis, regeneration and hypertrophy of skeletal muscles. The varied mechanisms orchestrated by AR collectively influence the physiology of skeletal muscles.